2016 Annual Conference on Information Science and Systems (CISS) 2016
DOI: 10.1109/ciss.2016.7460574
|View full text |Cite
|
Sign up to set email alerts
|

K users caching two files: An improved achievable rate

Abstract: Abstract-Caching is an approach to smoothen the variability of traffic over time. Recently it has been proved that the local memories at the users can be exploited for reducing the peak traffic in a much more efficient way than previously believed. In this work we improve upon the existing results and introduce a novel caching strategy that takes advantage of simultaneous coded placement and coded delivery in order to decrease the worst case achievable rate with 2 files and K users. We will show that for any c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Note that the above characterization of R s exactly matches a characterization of R * for a caching system with N files and N e (s) users. Specifically, the lower bound of R s given by (109) exactly matches Theorem 2, and the upper bound R dec (M, s) defined in (111) exactly matches the upper bound R dec (M ) defined in (16). Thus, by reusing the same arguments in the proof of Theorem 1 for the peak rate, we can easily prove that R s ≥ R dec (M, s)/2.00884 holds for the general case, and R s ≥ R dec (M, s)/2 holds for large N when…”
Section: Appendix B Proof Of Lemmasupporting
confidence: 53%
“…Note that the above characterization of R s exactly matches a characterization of R * for a caching system with N files and N e (s) users. Specifically, the lower bound of R s given by (109) exactly matches Theorem 2, and the upper bound R dec (M, s) defined in (111) exactly matches the upper bound R dec (M ) defined in (16). Thus, by reusing the same arguments in the proof of Theorem 1 for the peak rate, we can easily prove that R s ≥ R dec (M, s)/2.00884 holds for the general case, and R s ≥ R dec (M, s)/2 holds for large N when…”
Section: Appendix B Proof Of Lemmasupporting
confidence: 53%
“…There have also been several prior works considering caching designs with coded prefetching [10], [11], [13]- [15]. They focused on the centralized setting and showed that the peak communication rate achieved by uncoded prefetching schemes can be improved in some low capacity regimes.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent works extended it to decentralized caching placements [7], caching with nonuniform demands [8], online caching placements [9], hierarchical caching [10], caching with random demands [11], among other things. There have been significant research activities recently [12][13][14][15][16][17][18][19][20][21] in both refining the outer bounds and finding stronger codes for caching. Despite these efforts, the fundamental tradeoff had not been fully characterized except for the case with only two users and two files [6] before our work.…”
Section: Introductionmentioning
confidence: 99%